Resources for security and stability? The politics of regional Coopertion on the Mekong, 1957-2001 - Makim, Abigail (2002)
This article tells about the relationship between resource politics and security in international relations. Using the Mekong river Basin as its case study, the article examines the place of resource and development issues in attempts to develop regional institutions. The question of whether a resource development regime with apparently low productivity in terms of technical output, but high levels of resilience and longevity, should be considered a failure or not, is considered. This question is examined within the broader context of Southeast Asian politics during the First, Second, and Third Indochina conflicts as well as the post-cold war era. The article argues that survival and a capacity to change to meet the challenges of extreme broader events are clear evidence of regime success. From this standpoint, the article explores ways in which the Mekong resource regime is linked to more general concerns for political security and stability and way in fact reflect political concerns for subregional neighbourhood maintenance. - Reproduced.
Keywords: Regional Cooperation